Altered Feeding Behaviors and Adiposity Precede Observable Weight Gain in Young Rats Submitted to a Short-Term High-Fat Diet - Andrich, David E.; Melbouci, Lilya; Ou, Ya; Leduc-Gaudet, Jean-Philippe; Chabot, Francois; Lalonde, Francois; Lira, Fabio Santos [UNESP]; Gaylinn, Bruce D.; Gouspillou, Gilles; Danialou, Gawiyou; Comtois, Alain-Steve; St-Pierre, David H. (Hindawi Ltd, 2018)
Information regarding the early effects of obesogenic diets on feeding patterns and behaviors is limited. To improve knowledge regarding the etiology of obesity, young male Wistar rats were submitted to high-fat (HFD) or regular chow diets (RCDs) for 14 days. Various metabolic parameters were continuously measured using metabolic chambers. Total weight gain was similar between groups, but heavier visceral fat depots and reduced weight of livers were found in HFD rats. Total calorie intake was increased while individual feeding bouts were shorter and of higher calorie intake in response to HFD. Ambulatory activity and sleep duration were decreased in HFD rats during passive and active phase, respectively. Acylated and unacylated ghrelin levels were unaltered by the increased calorie intake and the early changes in body composition., is indicates that at this early stage, the orexigenic signal did not adapt to the high-calorie content of HFD. We hereby demonstrate that, although total weight gain is not affected, a short-term obesogenic diet alters body composition, feeding patterns, satiation, ambulatory activity profiles, and behaviours in a young rat model. Moreover, this effect precedes changes in weight gain, obesity, and ensuing metabolic disorders.